Pearls in the ribbed mussel Aulacomya atra caused by polydorin polychaetes (Spionidae) infestation - Diez, María Emilia (2016)
Aulacomya atra populations of the San Jose gulf, Northern Patagonia, Southwestern Atlantic Ocean, are infested by two polydorin species, Polydora rickettsi and Dipolydora cf. giardi. The infestation by these boring polychaetes causes the formation of pearls which is evidenced by the presence of capsules containing polydorin tissue debris and the elemental composition of organic material inside the pearls. Moreover, a positive relationship between the abundance of perforations of polydorin polychaetes and abundance of pearls was found by applying generalized lineal model analysis. These results constitute the first evidence of pearls formation due to infestation by polychaete.